2015
DOI: 10.1107/s1600576715004896
|View full text |Cite
|
Sign up to set email alerts
|

A look-up table based approach to characterize crystal twinning for synchrotron X-ray Laue microdiffraction scans

Abstract: An automated method has been developed to characterize the type and spatial distribution of twinning in crystal orientation maps from synchrotron X-ray Laue microdiffraction results. The method relies on a look-up table approach. Taking into account the twin axis and twin plane for plausible rotation and reflection twins, respectively, and the point group symmetry operations for a specific crystal, a look-up table listing crystal-specific rotation angle-axis pairs, which reveal the orientation relationship bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…For example, to measure crystal orientation, elastic strain distribution 32 , to distinguish between statistically stored dislocations (SSDs) and geometrically necessary dislocations (GNDs) 33 , to characterize the slip system of the GNDs 34 , to quantify dislocation densities 35 , one still needs to index the Laue pattern and analyze peak shape the usual way. Furthermore, although we demonstrate that the low angle grain boundaries are visible in the FIM, it is noted that from the FIM solely, it is difficult to distinguish between phase boundaries, low angle grain boundaries, high angle grain boundaries, and twin boundaries, and therefore it is necessary to index the Laue patterns 36 . An example containing both low and high angle grain boundaries is shown in Section 2 of the supplementary information .…”
Section: Discussionmentioning
confidence: 68%
“…For example, to measure crystal orientation, elastic strain distribution 32 , to distinguish between statistically stored dislocations (SSDs) and geometrically necessary dislocations (GNDs) 33 , to characterize the slip system of the GNDs 34 , to quantify dislocation densities 35 , one still needs to index the Laue pattern and analyze peak shape the usual way. Furthermore, although we demonstrate that the low angle grain boundaries are visible in the FIM, it is noted that from the FIM solely, it is difficult to distinguish between phase boundaries, low angle grain boundaries, high angle grain boundaries, and twin boundaries, and therefore it is necessary to index the Laue patterns 36 . An example containing both low and high angle grain boundaries is shown in Section 2 of the supplementary information .…”
Section: Discussionmentioning
confidence: 68%
“…In the polycrystalline region, the grains on the right side, which are closer to the edge of the specimen, are as narrow as 10–20 μm in the X -direction but elongated to up to 80 μm in Y -direction, while most of the grains farther away from the specimen edge are nearly equiaxed, with grain size ranging from 20 to 60 μm. Applying the approached developed previously 16 , we found that most of grain boundaries in this area are ordinary high angle ones, while twinning structures are only detected in a few grains.…”
Section: Resultsmentioning
confidence: 76%
“…The misorientation angle between the MC particles and matrix ranges from 5 to 60° (Fig. 1g), implying the incoherent nature of the boundaries between MC particles and γ/γ′ phase [27,28]. Both of the two grain boundaries observed in the studied region are tilt grain boundaries, and the misorientation angles are about 24°and 17°, respectively.…”
Section: Microstructural Characterization Near the Crack Regionmentioning
confidence: 99%